Rare Presentation of Severely Limited Granulomatosis With Polyangiitis Manifesting With Orbital Wall Destruction: Literature Review and Case Report - Erol HAVUZ; Seda GÜDÜL HAVUZ (Archives of Rheumatology, 2020)
Necrosis resulting from mechanical local factors can be seen in patients with granulomatosis with polyangiitis (GPA) even in remission. GPA can cause serious morbidity even when limited. An ocular prosthesis that increases inflammation and damages local circulation should be used very carefully in such patients. In this article, we report a 68-year-old male patient who was diagnosed with localized GPA 11 years ago and referred to our clinic with the complaint of displacement of an ocular prosthesis inside the nose and epistaxis. Four years ago, the left eye was enucleated because of pain and vision loss. Two months after the enucleation, the patient began to use an ocular prosthesis. Orbital medial wall destruction developed while the patient was receiving maintenance therapy that consisted of cyclophosphamide (150 mg/day) plus prednisolone (32 mg). When the ocular prosthesis was displaced in the nasal cavity, the prosthesis was first removed and the patient was clinically stabilized. Later, orbital wall reconstruction was performed at another center.